The Guarantees of the Public Employee in the Administrative Investigation (A Comparative Study between the Saudi System and the Egyptian Law) - Al-Thaqafi, Dareen Yousef (Journal of Economic, Administrative and Legal Sciences, 2024)
Administrative investigation represents the initial procedural stage of administrative disciplinary actions, encompassing a set of fundamental rules that validate this procedure and its consequent disciplinary sanctions. Foremost among these are the rules governing the guarantees for public employees during administrative investigations, which ensure that the investigation is conducted with fairness, integrity, and impartiality. However, the possibility of the investigating authority infringing upon the rights and guarantees of public employees is a concern. Thus, our research problem emerges from questioning the guarantees for public employees in administrative investigations within the Saudi system, aiming to establish a specific regulatory framework for these guarantees and to determine the legal consequences of their violation, ensuring the validity of the administrative investigation process and its disciplinary outcomes. Through employing both analytical and comparative methodologies, this study extracts the essential rules governing the guarantees for public employees in administrative investigations by analyzing legal texts and judicial decisions related to administrative disciplinary procedures in the Saudi system, comparing them with those in Egyptian law. Consequently, the concept of guarantees for public employees in administrative investigations, along with the substantive and formal fundamental rules organizing them, are discussed, including similarities and differences between the Saudi system and Egyptian law. The study concludes that the administrative disciplinary systems in both the Saudi and Egyptian legal frameworks lack a unified source that regulates all disciplinary procedures, leading to inconsistencies in rulings from one case to another. Additionally, it identifies the essential rules for guarantees in administrative investigations, which include substantive aspects like the right to defense, the principle of confrontation and impartiality, and formal aspects like the requirement for written investigations with basic information and the designation of a recorder to document the investigation proceedings.